PEMANFAATAN DUOLINGO UNTUK MENINGKATAKAN VOCABULARY SISWA - SISWI DI SMAN 11 GARUT - Hero Gunawan; Ervina CM Simatupang; Dianita Dianita; Puspita Sari; Deden Novan Setiawan Nugraha; Susiyanti Rusyan (LPPM Universitas Bina Bangsa, 2023)
This community service activity aims to train class XII students of SMAN 11 Garut on the benefits of the Duolingo application, which can be used as a tool for teaching and learning English. The method used in this activity is in the form of training and mentoring. The training and assistance provided in this activity use the Duolingo smartphone application. This service activity provides much pedagogical knowledge to class XII students and English teachers at SMAN 11 Garut so that they can learn or teach English in a fun way using the Duolingo application. Class XII students at SMAN 11 Garut said that the Duolingo application as an educational application is very useful when used in teaching and learning English in class